RUANG BIOSKOP RAMAH KURSI RODA - Tubalawony, Novinca Debora; Mustaram, Agnatasya Listianti (Jurusan Arsitektur dan Perencanaan, 2024)
Persons with disabilities still often experience various obstacles and limitations when seeking access to meet their needs, including difficulties in obtaining public services and facilities. There are only less than 30% of people with disabilities in Indonesia who can carry out activities in public independently so there is currently a need for government awareness to make changes and innovations in fulfilling and ensuring public services and facilities for people with disabilities. Entertainment and recreation facilities have become one of the important factors in people's lives today and watching in a movie theater is one of the most popular entertainment activities with the aim of entertaining themselves and providing pleasure when they feel bored. However, in terms of accessibility rights, the availability of cinema entertainment facilities and infrastructure is still minimal to provide a friendly space experience for people with physical disabilities. So this research will discuss the design of a friendly cinema space for people with physical disabilities who use wheelchairs. The research method used is descriptive qualitative research method with literature study approach and data development. With further elaboration, a discussion will be obtained regarding the design and application of design elements in the cinema room specifically for wheelchair users. The author hopes that this research can help to provide an ideal space experience for people with physical disabilities who use wheelchairs so that they can feel and enjoy cinema facilities safely and comfortably. Keywords: cinema; disabilities; wheelchair Abstrak Penyandang disabilitas masih sering mengalami berbagai rintangan dan keterbatasan ketika mencari akses untuk memenuhi kebutuhan mereka, termasuk kesulitan dalam mendapatkan layanan dan fasilitas publik. Hanya terdapat kurang dari 30% penyandang disabilitas di Indonesia yang dapat melakukan aktivitas di publik secara mandiri sehingga saat ini diperlukan kesadaran pemerintah untuk melakukan perubahan dan inovasi dalam memenuhi dan menjamin pelayanan dan fasilitas publik bagi penyandang disabilitas. Fasilitas hiburan dan rekreasi telah menjadi salah satu faktor penting dalam kehidupan masyarakat saat ini dan menonton di bioskop merupakan salah satu kegiatan hiburan yang banyak diminati dengan tujuan untuk menghibur diri dan memberikan kesenangan ketika sudah merasa jenuh. Namun dalam hak aksesibilitas, ketersediaan sarana dan prasarana hiburan bioskop masih minim untuk memberikan pengalaman ruang yang ramah bagi penyandang disabilitas fisik. Sehingga penelitian ini akan membahas desain ruang bioskop yang ramah bagi penyandang disabilitas fisik yang menggunakan kursi roda. Metode penelitian yang digunakan adalah metode penelitian deskriptif kualitatif dengan pendekatan studi literatur dan pengembangan data. Dengan penguraian lebih lanjut, akan diperoleh pembahasan mengenai rancangan dan penerapan elemen desain pada ruang bioskop yang dikhususkan untuk pengguna kursi roda. Penulis berharap agar penelitian ini dapat membantu untuk memberikan pengalaman ruang yang ideal bagi penyandang disabilitas fisik yang menggunakan kursi roda agar dapat merasakan dan menikmati fasilitas bioskop dengan aman dan nyaman.